Targeting of herpes simplex virus 1 thymidine kinase gene sequences into the OCT4 locus of human induced pluripotent stem cells. - Wu Ou; Pingjuan Li; Jakob Reiser (PLoS ONE, 2013)
The in vitro differentiation of human induced pluripotent stem cells (hiPSC) to generate specific types of cells is inefficient, and the remaining undifferentiated cells may form teratomas. This raises safety concerns for clinical applications of hiPSC-derived cellular products. To improve the safety of hiPSC, we attempted to site-specifically insert a herpes simplex virus 1 thymidine kinase (HSV1-TK) suicide gene at the endogenous OCT4 (POU5F1) locus of hiPSC. Since the endogenous OCT4 promoter is active in undifferentiated cells only, we speculated that the HSV1-TK suicide gene will be transcribed in undifferentiated cells only and that the remaining undifferentiated cells can be depleted by treating them with the prodrug ganciclovir (GCV) prior to transplantation. To insert the HSV1-TK gene at the OCT4 locus, we cotransfected hiPSC with a pair of plasmids encoding an OCT4-specific zinc finger nuclease (ZFN) and a donor plasmid harboring a promoter-less transgene cassette consisting of HSV1-TK and puromycin resistance gene sequences, flanked by OCT4 gene sequences. Puromycin resistant clones were established and characterized regarding their sensitivity to GCV and the site of integration of the HSV1-TK/puromycin resistance gene cassette. Of the nine puromycin-resistant iPSC clones analyzed, three contained the HSV1-TK transgene at the OCT4 locus, but they were not sensitive to GCV. The other six clones were GCV-sensitive, but the TK gene was located at off-target sites. These TK-expressing hiPSC clones remained GCV sensitive for up to 90 days, indicating that TK transgene expression was stable. Possible reasons for our failed attempt to selectively target the OCT4 locus are discussed.